Prospects of plant-based systems as an ecotechnological approach for heavy metals removal from polluted-waters - Pérez, Leonardo Martín (2021)
Fil: Pérez, Leonardo Martín. Pontificia Universidad Católica Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Grupo de Biotecnología de Materiales y Medioambiente; Argentina